Advancing the State of Mobile Cloud Computing - Bahl, Victor; Han, Richard Y.; Li, Li Erran; Satyanarayanan, Mahadev (Proceedings of the third ACM workshop on Mobile Cloud Computing and Services, (MCS), Low Wood Bay, Lake District, UK, June 2012, 2012)
The capabilities of mobile devices have been improving very quickly in terms of computing power, storage, feature support, and developed applications. However, these mobile applications are still intrinsically limited by a relative lack of bandwidth, computing power, and energy compared to their tethered counterparts. Cloud computing offers abundant computing power that can be tapped easily. Apple iCloud and Amazon Silk browser are two recent mobile applications that leverage the cloud. In this paper, we systematically explore the fundamental research questions when combining mobile and cloud computing. We will highlight some of the challenges we face and some of the solutions we are pursuing.